2020
DOI: 10.35575/rvucn.n61a9
|View full text |Cite
|
Sign up to set email alerts
|

Auto-ocultación del acoso escolar si se es víctima, agresor o testigo, y su vinculación con el bienestar subjetivo

Abstract: El bullying es un comportamiento muy frecuente y ocurre sin ninguna provocación aparente por parte de quien lo sufre. Con el objeto de analizar cómo influye la auto-ocultación sobre el bienestar subjetivo, cuando se está implicado en situaciones de acoso escolar, se realizó una investigación con una muestra de 299 estudiantes, en centros de Lanzarote (Canarias, España), a través de un diseño correlacional donde cada alumno se auto-identifica como víctima, agresor o testigo. Los participantes tenían una media d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Other studies have reported similar findings of differences between the genders [27,[68][69][70][71][72][73][74]. The gender of students has been found to be a fundamental variable to consider when studying bullying [56], including cyberbullying [75,76], particularly with regard to internalization and externalization of violent behaviors and attitudes [77], and it is important to include the analysis of the greater vulnerability to bullying in LGTB students [78].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Other studies have reported similar findings of differences between the genders [27,[68][69][70][71][72][73][74]. The gender of students has been found to be a fundamental variable to consider when studying bullying [56], including cyberbullying [75,76], particularly with regard to internalization and externalization of violent behaviors and attitudes [77], and it is important to include the analysis of the greater vulnerability to bullying in LGTB students [78].…”
Section: Discussionmentioning
confidence: 82%
“…Finally, a multivariate analysis between the sex variable and each dimension and the total score in the questionnaire confirmed these statistically significant differences, with values of p < 0.001 (Concept dimension F = 876.79, p = 0.000; Perception dimension F = 1662.43, p = 0.000; Skills dimension F = 1165.13, p = 0.000; Total F = 2842.42, p = 0.000). Student gender is a variable to bear in mind both at the preventive level and in specific interventions in situations of bullying and cyberbullying [48][49][50][51]56].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different actors that appear in bullying situations, the victims of this type of violence present the greatest difficulties and problems related to their involvement in bullying situations. These difficulties can appear in the academic (low performance, absenteeism, dropping out of school), physical (hitting, scratching, pushing, among others) and psychological (low self-esteem and well-being, depression, social isolation and in some cases even suicide) areas [12]. The victim role is statistically related to internalizing and externalizing problems [13], including low psychological well-being and social adjustment and high levels of psychological stress [14].…”
Section: The Current Studymentioning
confidence: 99%